Institutional incentives for altruism: gifting blood in China - Yu, Chengpu (BioMed Central, 2013)
BACKGROUND: In mainland China, the motivation behind voluntary blood donation is a relatively new and understudied behavior. In recent times provincial governments in China have implemented various institutional incentive measures. However, little is known regarding the effectiveness of such measures. This qualitative study investigated the nature and outcomes of some identified institutionalized mechanisms, in particular how these were created and distributed in the form of incentives for voluntary blood donation. METHODS: Participatory observations were conducted at two blood donation stations and four blood collecting vehicles in Changsha city, China. In-depth interviews were conducted with 17 staff and 58 blood donors at the aforementioned venues from May to October 2008 in Changsha. RESULTS: Thematic analysis revealed the operation of four primary type incentives: policy-driven, symbolic, information feedback and role models, which constituted the system of institutional incentives. The current blood reimbursement system was not the primary motivation for blood donation; instead this system was a subtheme of future assurance for emergency blood needs. It was evident that symbolic incentives stressed the meaning and value of blood donation. Furthermore, post-donation information services and the inherent mechanisms of communication, enhanced by some public role models, served to draw the public to donate blood. CONCLUSIONS: At the institutional level, blood donation was not only informed by altruism, but also carried a system of benefit and reward for the donors and their family members. We would recommend that such arrangements, if accommodated effectively into China’s health promotion strategies, would increase the likelihood of blood donation.